(untitled) (Research, Society and Development, 2024)
Orofacial clefts are common congenital defects affecting the structure of the lip and/or palate, leading to significant impacts on health, quality of life, and socioeconomic well-being of affected individuals and their families. Among craniofacial malformations, cleft lip and palate are the most prevalent, with surgical treatment typically initiated in the first months of life and potentially extending into adulthood. However, despite surgical interventions, some patients may develop residual oronasal fistulas of varying sizes. Although multiple approaches are available for closing these fistulas, the palatal flap rotation technique remains underexplored in this context within the literature, despite its extensive application in the closure of post-extraction fistulas. This study presents a case report in which a patient with a cleft lip and palate underwent late-stage closure of an oronasal fistula, utilizing leukocyte- and platelet-rich fibrin (L-PRF) as an adjunct, aiming to enhance soft tissue healing. Although the technique used did not achieve complete closure of the oronasal fistula, this case report contributes to the understanding of the limitations and potential of combining L-PRF with the palatal flap. Further studies are needed to refine this approach for patients with cleft lip and palate and residual fistulas.